The effects of the method of formation of drawing on the acquisition of graphic activity in preschoolers - María Raquel Ramírez Barreda; Yulia Solovieva; Luis Quintanar Rojas (Современное дошкольное образование)
Background. Preschool age is a period of great importance for psychological development and preparation for school. One of the activities that must be formed in preschool age is visual activity, which is of great importance for the overall development of a preschooler. Involving children in visual activity is a step necessary for forming a solid neuropsychological foundation that will determine their success not only at school, but also in life in general.